ANALYSIS OF THE EFFECT OF PERSONALITY ON TURNOVER INTENTION BASED ON EMOTIONAL DATA: A CASE STUDY OF JOB BURNOUT AND EMPLOYEE ENGAGEMENT AT PT. SEJAHTERA KURIR EXPRESS CIREBON - Suci Fitaloka Putri; Kartono Kartono (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of personality on turnover intention, with job burnout and employee engagement serving as mediating variables at PT Sejahtera Kurir Express Cirebon. The increasing rate of employee turnover since 2023 constitutes the primary background of this research. This study employs a quantitative explanatory approach with a sample of 151 respondents selected using purposive sampling techniques. Data were collected through an online questionnaire and analyzed using path analysis with SPSS 29. The results indicate that personality has a significant effect on both job burnout and employee engagement. Furthermore, job burnout, employee engagement, and personality significantly influence turnover intention. Interestingly, employee engagement shows a positive relationship with turnover intention, suggesting that highly engaged employees may seek better career opportunities when organizational support is insufficient. In addition, job burnout and employee engagement significantly act as mediating variables in the relationship between personality and turnover intention. These findings highlight the importance of managing employees’ psychological conditions and providing adequate organizational support to reduce employee turnover rates.